Revenue Management for the Hospitality Industry / David K. Hayes, Allisha Miller - David K. Hayes
Revenue Management for the Hospitality Industry is filled with practical examples and best practices on the topic of revenue management, a critical aspect of the industry. Through numerous revenue management examples from the hospitality industry and a running case example throughout the book, students will discover how they can incorporate revenue management principles and best practices. The core of revenue management of a hospitality organisation is to, as the authors explain, "charge the right price, to the right customer, for the right product, through the right channel, at the right time." The book is intended for students with prior knowledge and understanding of the hospitality industry, and will explain what they need to know and how to be successful.